Mismatch repair deficiency, chemotherapy and survival for resectable gastric cancer: an observational study from the German staR cohort and a meta-analysis - Stolze, T.; Franke, S.; Haybaeck, J.; Moehler, M.; Grimminger, P. P.; Lang, H.; Roth, W.; Gockel; Kreuser, N.; Blaker, H.; Wittekind, C.; Lordick, F.; et al. (Journal of Cancer Research and Clinical Oncology, 2022)
Purpose: In a post hoc analysis of the MAGIC trial, patients with curatively resected gastric cancer (GC) and mismatch repair (MMR) deficiency (MMRd) had better median overall survival (OS) when treated with surgery alone but worse median OS when treated with additional chemotherapy. Further data are required to corroborate these findings. Methods: Between April 2013 and December 2018, 458 patients with curatively resected GC, including cancers of the esophagogastric junction Siewert type II and III, were identified in the German centers of the staR consortium. Tumor sections were assessed for expression of MLH1, MSH2, MSH6 and PMS2 by immunohistochemistry. The association between MMR status and survival was assessed. Similar studies published up to January 2021 were then identified in a MEDLINE search for a meta-analysis. Results: MMR-status and survival data were available for 223 patients (median age 66 years, 62.8% male), 23 patients were MMRd (10.3%). After matching for baseline clinical characteristics, median OS was not reached in any subgroup. Compared to perioperative chemotherapy, patients receiving surgery alone with MMRd and MMRp had a HR of 0.67 (95% CI 0.13–3.37, P = 0.63) and 1.44 (95% CI 0.66–3.13, P = 0.36), respectively. The meta-analysis included pooled data from 385 patients. Compared to perioperative chemotherapy, patients receiving surgery alone with MMRd had an improved OS with a HR of 0.36 (95% CI 0.14–0.91, P = 0.03), whereas those with MMRp had a HR of 1.18 (95% CI 0.89–1.58, P = 0.26). Conclusion: Our data support a positive prognostic effect for MMRd in GC patients treated with surgery only and a differentially negative prognostic effect in patients treated with perioperative chemotherapy. MMR status determined by preoperative biopsies may be used as a predictive biomarker to select patients for perioperative chemotherapy in curatively resectable GC.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Chemotherapy; Gastric cancer; Meta-analysis; Mismatch repair deficiency; Survival

Prevalence of Histological Gastritis in a Community Population and Association with Epigastric Pain - Zuzek, Rachael; Potter, Michael; Talley, Nicholas J.; Agréus, L.; Andreasson, A.; Veits, Lothar; Vieth, Michael; Walker, M. M. (Digestive Diseases and Sciences, 2023)
Background and Aims: Gastritis is a common histological diagnosis, although the prevalence is decreasing in developed populations, alongside decreasing prevalence of H. pylori infection. We sought to determine the prevalence of the etiology of gastritis in a Swedish population sample and to analyze any associations with symptoms, an area of clinical uncertainty. Methods: Longitudinal population-based study based in Östhammar, Sweden. A randomly sampled adult population completed a validated gastrointestinal symptom questionnaire (Abdominal Symptom Questionnaire, ASQ) in 2011 (N = 1175). Participants < 80 years of age and who were eligible were invited to undergo esophagogastroduodenoscopy (EGD) (N = 947); 402 accepted and 368 underwent EGD with antral and body biopsies (average 54.1 years, range 20–79 years; 47.8% male) with H. pylori serology. Results: Gastritis was found in 40.2% (148/368; 95% CI 35.2–45.2%). By rank, the most common histological subtype was reactive (68/148; 45.9%), then H. pylori (44/148; 29.7%), chronic non-H. pylori (29/148; 19.6%), and autoimmune (4/148; 2.7%). Gastritis was significantly associated with older age and H. pylori status (p < 0.01). Gastritis subjects were divided into three histological categories: chronic inactive inflammation, autoimmune gastritis, and active inflammation; there was no difference in the presence of upper gastrointestinal symptoms when categories were compared to cases with no pathological changes. Functional dyspepsia or gastroesophageal reflux were reported in 25.7% (38/148) of those with gastritis (any type or location) versus 34.1% (75/220) with no pathological changes (p = 0.32). Epigastric pain was more common in chronic H. pylori negative gastritis in the gastric body (OR = 3.22, 95% CI 1.08–9.62). Conclusion: Gastritis is common in the population with a prevalence of 40% and is usually asymptomatic. Chronic body gastritis may be associated with epigastric pain, but independent validation is required to confirm these findings. Clinicians should not generally ascribe symptoms to histological gastritis.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Endoscopy; Epigastric pain; Gastritis; H. pylori; Prevalence